IMPLEMENTATION OF STALL HEALTH PROTOCOLS IN TOURIST AREA - Kurniawan, Dian; Soeaidy, Mohammad Soleh; Ardiani, Gusti Tia; Mandasari, Andina Eka (Inaba of Community Services Journal, 2023)
At the beginning of 2020, the world was shocked by the emergence of the Covid-19 virus, which spreads so massively and quickly and has fatal consequences for the human body. This has forced the world to make many changes, including making contact with humans to avoid the broader spread of the virus. These social restrictions have a significant impact on people's lives, one of the most felt impacts is the increasingly sluggish economic and business activities in Indonesia, including the tourism sector. As one element of a tourist location, stalls in tourist attractions must implement the CHSE (Cleanliness, Health, Safety, Environment Sustainability) protocol initiated by the Ministry of Tourism and Creative Economy to ensure the safety of tourists who want to explore Indonesia. Therefore, an idea was made as a problem solver for stall business actors to understand and apply health protocols in every business activity. This activity provides guidance in the form of counselling and assistance regarding the application of standard health protocols in business activities during the transition period of the Covid-19 pandemic. This is intended to reduce the risk of spreading the Covid-19 virus. In addition, this service activity can be one of the activities that provide practical benefits for stall business actors so that they can continue to carry out business activities during the transition period of the Covid-19 pandemic.